State aid for broadband network deployment: National and subnational governance mechanisms, 2003-2023 - Manica, L.; Damásio, B.; Mendonça, S. (Telecommunication Policy, 2024)
This paper examines the governance models of State aid measures for broadband network deployment in European Union Member States. The research is based on 199 decision letters collected from the European Commission's competition cases database, published between 2003 and 2023. Deploying a theory-driven content analysis approach, the analysis reveals and categorises a variety of governance models. These models vary regarding the authority responsible for the decision-making and, in the case of national schemes, the authority responsible for the implementation, including centralised and decentralised arrangements. Different legacies and institutional set-ups explain the governance models, including the typology of state structures, the constitutional powers, the traditions of participation in the telecommunication sector, policy diffusion and regional development. There are several possible pathways to a gradual transition from one model to another. The design of flexible national schemes, which offer subnational authorities the option to implement them in their regions or to rely on central management agencies for specific tasks adapted to their interests, resources and capacities, could be the optimal solution to prevent the launch of ad hoc measures by subnational authorities and to adapt to different institutional arrangements.